Вы находитесь на странице: 1из 20

www.sakshieducation.com

TRANSFORMATIONS

1. sin C + sin D = 2sin

 C + D C − D . cos . 2 2
C + D
C
− D .
2. sin C – sin D = 2cos
. sin
2 2
C
+ D
C − D .
3. cos C + cos D = 2cos
. cos
2
2
C
+ D
D − C .
4. cos C – cos D = 2sin
.
sin
2
2
5. 2sin A cos B = sin(A + B) + sin(A – B)
6. 2cos A sin B = sin(A + B) – sin(A – B)
7. 2cos A cos B = cos(A + B) + cos(A – B)
8. 2sin A sin B = cos(A – B) – cos(A + B)
(or)
cos(A – B) – cos(A + B) = 2 sin A sin B.
9. sin A
sin B
A + B ).
+ = tan(
sin A
− sin B
2
10. If sin A + sin B = x, and cos A + cos B = y. Then
A + B ) =
x
i) tan(
2
y
2xy
ii) sin(A + B) =
2
2
y
+ x
2
2
y
− x
iii) cos(A + B) =
2
2
y
+ x
2xy
iv) tan(A + B) =
2
2
y
− x

www.sakshieducation.com

www.sakshieducation.com

VSAQ’S

Solution:

1.

Prove that

sin50 −+=sin 70

sin10

0

00

0

00
00
⎛ 50
+
70
50
70
0
00
0
sin 50
−+=
sin 70
sin10
2cos
2
⎟⎜ ⎞⎛ sin
⎠⎝
+
sin10
2
00
(
)
0
= 2cos 60 sin −+10 sin10
1
00
0
0
= − 2 ×
sin10
+ sin10
=− sin10
+ sin10
= 0
2
0
0
sin 70
− cos 40
1
2. Prove that
=
0
0
cos50
− sin 20
3
0
0
00
0
0
sin 70
− cos 40
sin 70
sin 50
2 cos 60 .sin10
1
=
=
=
00
0
0
0
0
cos50
sin 20
cos50
cos 70
2 sin 60 .sin10
3
3.
Prove that cos 55° + cos 65° + cos 175° = 0
Sol. cos 55° + cos 65° + cos 175°
°
⎛ 55
°+
65
55
°−
65
°
=
2cos
⎜ ⎝
2
⎟⎜ ⎞⎛ cos
⎠⎝
2
⎟ ⎠
+
cos(180
°−
5 )
°
=
2cos 60 ° cos(
−°− 5 )
cos5
°
1
=
2
×
cos5
°−
cos5
°=
0
2
3
+
1
4.
Prove that
cos 20 ° cos 40
°−
sin 5 ° sin 25
°=
.
4
Sol. cos 20° cos 40°− sin 5°sin 25°
=
1 [2cos 40 ° cos 20
2
°−
2sin 25
°
sin 5 ° ]
=
1 [cos(40
°+
20 ° )
+
cos(40
°−
20 ° )
2
+
cos(25
°+
5 ° )
cos(25
°−
5 ° )]
= [cos 60
2
1 cos 20
°+
°+
cos30
°−
cos 20 ° ]
= °+
1 cos30 ° ]
2
[cos 60
11 ⎡
3
31
+
=+=
22 ⎣
2
4

www.sakshieducation.com

www.sakshieducation.com

4 {
0
0
5. Prove that
cos 66
+ sin 84
}
=+3
5
Solution:
{
00
0
4
cos 66
+=sin 80
}
4 cos 66
{
0
+ cos 66
}{
0
0
∵ sin 84
= cos 66
}
5
+
1
3
=
4
{
0
0
2cos36 . cos30
}
= 8
=
3 +
15
4
2
⎟ ⎟ ⎠
3
+
5
0
0
6.
Prove that
cos 48 cos12
=
8
Solution:
1
1
00
cos 48 cos12
=
{
0
0
}
0
2cos 48
{
0
+= cos12
cos 60
+
cos36
}
2
2
11
5
+
1
2
++
5
1
5
+
3
+=
=
22
4
8
8
⎪ ⎩
⎪ ⎭
1
2
2
2
7.
Prove that
sin (α− 45°) + sin (α+15°) −
sin
(
α−
15 ) =
°
.
2
2
22
Sol.
sin (α− 45°) + sin (α+15°) − sin (α−15°)
2
2
=
sin
(
α−
45 )
°
+
sin
(
α+
15
°+α−
15 )
°
sin(
α+
15
−α+
15)
2
=
sin
(
α−
45
°
)
+
sin 2
α⋅
sin 30
°
1 cos(2
α−
90 ° )
sin 2
α
=
+
2
2
1 sin 2
α+
sin 2
α
1
=
=
2
2
8.
Prove that
cosθθ+ cos 120
(
0
0
++ cos 240
)(
+=θ
)
0
Solution:
0
0
⎛ 120
θ
+
240
+
θ
0
0
cos
θ
+
cos 120
(
−+
θ
)(
cos 240
−=
θθ
)
cos
+
2cos
2
0
0
⎛ 120
+θ −
240
θ
cos
2
1
0
0
=
cos
θ +
2 cos 180
(
+−θ
)
cos 60
()
=
cos
θθ−
2 cos
×
2
=−=cosθ cosθ 0

www.sakshieducation.com

www.sakshieducation.com

1
1
9.
If sin x
+
sin y
=
and
cos x
+
cos y
=
, then show that
4
3
xy
+
3
7
(i)
tan
, (ii)
cot(x
+
y)
=
.
⎜ ⎝
2
⎞ ⎟ ⎠ =
4
24
1
Sol. i)
sin x
+
sin y
=
…(1)
4
1
cos x
+
cos y
=
…(2)
3
⎛ xy
+
xy
1
(1)
2sin
⎜ ⎝
2
⎟⎜ ⎞⎛ cos
⎠⎝
=
(3)
24 ⎠ ⎟
⎛ xy
+
xy
1
(2)
2cos
⎟⎜ ⎞⎛ cos
⎠⎝
=
(4)
⎜ ⎝
2
23 ⎠ ⎟
(3)
Dividing
, we get
(4)
xy
+
xy ⎞
2sin
⎟⎜ ⎞⎛ cos
2
⎠⎝
2
⎟ ⎠
1
3
=
×
xy
+
xy ⎞
4
1
2cos
⎟⎜ ⎞⎛ cos
2
⎠⎝
2
⎠ ⎟
⎛ xy
+
3
tan
⎜ ⎝
2
⎞ ⎟ ⎠ =
4
⎛ xy
+
3
ii) Let
tan
=
t
⎝ ⎜
2
⎞ ⎟ ⎠ =
4
3
2
2t
⎜ ⎝
4
⎟ ⎠
24
tan(x
+= y)
=
=
2
9
1
t
7
1 −
16
1
7
cot(x
+= y)
=
tan(x
+
y)
24
10.
(i) tan
⎛ x + y ⎞
If sin x + sin ya= and cos x + cos yb= find the values of
⎛ x − y ⎞
(ii) sin
2
⎠ ⎟
⎝ ⎜
2
⎟ ⎠
Solution:
x
+
y
xy ⎞
2sin
⎟⎜ ⎞⎛ cos
sin
x
+ y
sin
a
2
⎠⎝
2
⎟ ⎠
a
=
=
cos
x
+ yb
cos
xy
+
xy ⎞
b
2cos
⎟⎜ ⎞⎛ cos
2
⎠⎝
2
⎠ ⎟
⎛ x
+
y
a
tan
⎜ ⎝
2
⎞ ⎟ ⎠ =
b

(

sin x + sin y + cos x + cos yab=+

)(

2

)

2

2

2

sin x + sin y + 2sin x sin y + cos x + cos y + 2cos x cos ya=+ b

2

2

2

2

22

www.sakshieducation.com

www.sakshieducation.com

(

1

sin

2

x + cos

2

++ 1

2 cos

(

x

x

)(

+

y

)

sin

2

=

a

2

y + cos

2

+

b

2

y

)

+ 2 cos x cos y + sin x + sin yab=+

{

}

22

cos

()

xy

=

a

2

+

b

2

2

2

y
(
⎛ x
cos
x
y
)
2
sin
1
(
22
4
a
b
)
/ 4
⎜ ⎝
2
⎞ ⎟ ⎠ =
2
1
−+−
cos
A
cos
B
cos
(
AB +
)
A
B
11.
Prove that
= tan
cot
1
+
cos
A
−−
cos
B
cos
(
AB
+
)
2
2
Solution:
1
−+−
cos
A
cos
B
cos
(
AB +
)
{
1
cos
(
AB
+−
)
{
cos
A
cos
B
}}
=
1
+−−
cos
A
cos
B
cos
(
AB +
)
{
1
cos
(
AB
++
){
cos
A
cos
B
}}
AB
+
AB
+−
⎞⎛
AB
⎛ AB
++⎞⎛⎧
AB
AB ⎞⎫
+
2
2
2sin
+ 2sin
⎟⎜ sin
2sin
⎟⎜ ⎨ sin
+
sin
2
2
⎟ ⎠
⎜ ⎝
22 ⎠⎝
⎟ ⎠
⎜ ⎝
22 ⎠⎝⎩
⎠ ⎟
⎝ ⎜
⎠⎭ ⎟
=
⎛ A
+
B
A
+−⎞⎛
B
AB ⎞
⎛ A
++−⎞⎛⎧
B
AB
A
B
⎞⎫
2
2sin
− 2 sin
⎟⎜ sin
2sin
⎟⎜ ⎨ sin
sin
2
⎟ ⎠
⎝ ⎜
22 ⎠⎝
⎠ ⎟
⎜ ⎝
22 ⎠⎝⎩
⎠ ⎟
⎜ ⎝
2
⎠⎭
A
B
2sin
cos
A
B
2
2
tan
cot
A
B =
2
2
2cos
sin
2
2

www.sakshieducation.com

www.sakshieducation.com

SAQ’S

12.
If neither (A – 15°) nor (A – 75°) is an integral multiple of 180°, prove that
4cos 2A
cot(15° – A) + tan(15° + A) =
1− 2sin 2A .
cos(15
°−
A)
sin(15
°+
A)
Sol.
cot(15° – A) + tan(15° + A)
=
+
sin(15
°−
A)
cos(15
°+
A)
cos(15
°−
A)cos(15
°+
A)
+
sin(15
°+
A)sin(15
°−
A)
=
sin(15
°−
A)cos(15
°+
A)
22
2
2
2 ⎡ ⎣ (cos
A
sin
15 ° )
+
sin (15
°−
sin
A)
⎤ ⎦
=
[
2cos(15
°+
A)sin(15
°−
A)
]
2
2
2(cos
A
sin
A)
=
sin(15
°+
A
+
15
°−
A)
sin(15
°+
A
15
°+
A)
2
2
2(cos A
sin
A)
=
sin 30
°−
sin 2A
2cos 2A
4cos 2A
=
=
1
1
2sin 2A
− sin 2A
2
13.
Prove that 4cos12°cos 48°cos 72°= cos36° .
Sol.
4cos12°°°cos 48 cos 72
=
(2cos 48 °° cos12 )(2cos 72 ° )
=
[cos(48
++ 12)
cos(48
12)]2cos 72
°
=
[cos 60
°+
cos36 ° ]2cos 72
°
=
2cos 60 ° cos 72
°+
2cos36 ° cos 72
°
1
=
2
×
cos 72
°+
cos(72
°+
36 ° )
+
cos(72
°−
36 ° )
2
=
cos 72
°+
cos108
°+
cos36
°
=
cos(90
°−
18 ° )
+
cos(90
°+
18 ° )
+
cos36
°
=
sin18
°−
sin18
°+
cos36
°
=
cos36
°
14.
Prove that sin10°+ sin 20°+ sin 40°+ sin 50°= sin 70°+ sin 80°
Sol. sin10°+ sin 20°+ sin 40°+ sin 50°
°
10
°+
20
°
⎞⎛
10
°−
20
40
°+
50
°
⎞⎛
40
°−
50
°
=
2sin
cos
+
2sin
cos
⎟⎜
⎟⎜
⎜ ⎝
22
⎠⎝
⎟ ⎠
⎜ ⎝
22
⎠⎝
⎟ ⎠
=
2sin15 cos5
°
°+
2sin 45 cos5
°
°
=
2cos5 [sin15
°
°+
cos 45
°
]

= 2cos5

°

2sin

15

⎜ ⎝

°+

45

° ⎞⎛

⎟⎜ cos

⎠⎝

15

°−

45

° ⎞⎤

⎟⎥ ⎠⎦

2

2

www.sakshieducation.com

www.sakshieducation.com

= 2cos5 ° [2sin 30 °° cos15 ]

 = 4cos5 °⋅ 1 cos15 °= 2cos15 ° cos5 ° 2
=
cos(15
+
5)
+
cos(15
5)
=
cos 20
°+
cos10
°
=
cos(90
°−
70 ° )
+
cos(90
°−
10 ° )
=
sin 70
°+
sin80
°
15.
If none of the denominators is zero, prove that
A
B
n
n
n
cos A
+
cos B
⎤⎡
sin A
+
sin B ⎤
2
cot
, if n is even
+
= ⎨
⎜ ⎝
2
.
⎥⎢
⎢ ⎣
sin A
sin B
⎦⎣
cos A
cos B
⎟ ⎠
⎩ 0, if n is odd
n
n
n
cos A
+
cos B
⎤⎡
sin A
+
sin B ⎤
AB
+
AB
⎞ ⎤
AB
+
AB ⎞ ⎤
2cos
⎟⎜ ⎞⎛ cos
2sin
⎟⎜ ⎞⎛ cos
Sol.
+
⎥⎢
⎥⎢
22 ⎠⎝
⎟ ⎠
⎝ ⎜
22 ⎠⎝
⎠ ⎟
⎣ ⎢
sin A
sin B
⎦⎣
cos A
cos B
= ⎢
⎥⎢+
AB
+−⎞⎛
AB
AB
+−⎞⎛
AB ⎞
⎥⎢
2cos
⎟⎜ sin
2sin
⎟⎜ sin
22 ⎠⎝
⎠ ⎦⎣ ⎥⎢
⎝ ⎜
22 ⎠⎝
⎠ ⎦ ⎥
⎛⎞− AB
⎛⎞− AB
n
nn
=
cot
+−
(
1)
cot
=
0
⎜⎟
⎜⎟
⎝⎠ 2
if n is odd, since (–1) n = –1
⎝⎠
2
A
B
n
= 2cot
⎠ ⎟ if n is even, since (–1) n =1
2
4
2
16.
If
cos
x +=y
cos
and
cos
x −=y
cos
then find the value of
5
7
⎛⎞xy−
⎛⎞xy+
14 tan
+
5cot
⎜⎟
⎜⎟
⎝⎠ 2
⎝⎠ 2
Solution:
4
⎛ xy
+
⎞⎛
xy ⎞
2cos
cos
+ ⎜⎟
2
cos
x
cos
y
⎝⎠
5
⎜ ⎝
2
⎟ ⎠
⎜ ⎝
2
⎟ ⎠
4
7
=
=
×
cos
x
− ⎛⎞
cos
y
2
⎛ xy
+
xy ⎞
5
2
− 2sin
sin
⎟⎜
⎝ ⎜
5
⎠ ⎟
⎝ ⎜
2
⎠⎝
2
⎠ ⎟
⎛ x
+
y ⎞
− cot
2
14
⎛ x
y
⎛⎞− xy
⎠ =
⇒ −
5cot
=
14 tan
⎜⎟
⎛ x
y ⎞
52
⎠ ⎟
⎝⎠
2
tan
⎜ ⎝
2
⎟ ⎠
⎛⎞xy−
⎛⎞xy+
14 tan
+
5cot
=
0
⎜⎟
⎜⎟
⎝⎠ 2
⎝⎠ 2
17.
If sec()()θα++ sec θα−= 2secθ and cosα ≠ 1 then show that
α
cos
θ = ±
2cos
2
Solution:

sec()()θα++ sec θα−= 2secθ

1

cos

(

θα

+

)

+

 12 = cos ()() θα −+ cos θα + = 2 cos ( θα − ) cos θ ⇒ cos ( θα −+ cos )( θα ) cos θ

www.sakshieducation.com

www.sakshieducation.com

(

2 cosθαcos

)

cosθ = 2

{

2

cos θ sin

2

}

α

2

cos θαcos

22

= cos θ sin

α sin

2

α = cos θ 1 cosα

2

(

)

(
1
cos
α
) (
1
+
cos
α
)
α
2
cos
θ
=
cos
θ = ±
2 cos 2
(
1
cos
α
)
18. If sin A = sin B and cos A = cos B, then prove that A = 2nπ + B for some
integer n.
Sol.
sin A = sin B and cos A = cos B
sin A
−=
sin B
0 and cos A
cos B
=
0
⎛ AB
+
AB ⎞
2cos
⎟⎜ ⎞⎛ sin
⎠⎝
=
0 and
⎝ ⎜
2
2
⎟ ⎠
⎛ AB
+
AB ⎞
2sin
=
0
⎝ ⎜
2
⎟⎜ ⎞⎛ sin
⎠⎝
2
⎠ ⎟
⎛⎞− AB
⎛⎞− AB
sin
=
0 and sin
=
0
⎜⎟
⎜⎟
⎝⎠ 2
⎝⎠ 2
A
B
=
n
π
2
A
−= B
2n
π ⇒
A
=
2n
π+
B (n
Z)
19. If cos nα ≠ 0 and cos
α ≠
0 , then show that
2
sin(n
+
1)
α−
sin(n
1)
α
α
=
tan
cos(n
+
1)
α+
2cos n
α+
cos(n
1)
α
2
Sol. Let cos nα ≠ 0 and cos
α ≠
0
then
2
cos(n
+
1)
α+
2cos n
α+
cos(n
1)
α
=
cos(n
α+α ) +
cos(n
α−α ) +
2cos n
α
=
2cos n
α
cos
α+
2cos n
α
=
2cos n α+ [1
cos
α
]
α
2
=
4cos
cos n
α≠
0
2
sin(n
+
1)
α−
sin(n
1)
α=
sin(n
α+α ) −
sin(n
α−α
)
=
2cos n
αα sin
α
α
=
4cos n
α
sin
cos
2
2
sin(n
+
1)
α−
sin(n
1)
α
cos(n
+
1)
α+
2cos n
α+
cos(n
1)
α

=

α
4cos n
α
sin
αα cos
sin
α
22
2
== tan 2
α
α
2
4cos
cos n
α
cos
2
2

www.sakshieducation.com

www.sakshieducation.com

20. If none of x, y, z is an odd multiple of π/2 and if sin(y + z – x), sin(z + x – y),

sin(x + y – z) are in A.P., then prove that tan x, tan y, tan z are also in A.P.

Sol. sin(y + z – x), sin(z + x – y), sin(x + y – z) are in A.P.

sin(z
+− x
y)
sin(y
+− z
x)
=
sin(x
+− y
z)
sin(z
+− x
y)
⎛ zxyyzx +−++−
zxyyzx +−−−+ ⎞
⇒ 2cos
⎝ ⎜
2
⎟⎜ ⎞⎛ sin
⎠⎝
2
⎠ ⎟
⎛ xyzzxy
+−++−
xyzzxy ⎞
+−−−+
= 2cos
⎟⎜ ⎞⎛ sin
2
2
⎠ ⎟
2cos zsin(x
−= y)
⎠⎝
2cos x sin(y
z)
2cos z[sin x cos y
cos x sin y]
=
2cos x[sin y cos z − cos ysin z]
Dividing with cosx cosy cosz, we get
2cos z[sin x cos y
cos x sin y]
2cos x[sin y cos z
cos ysin z]
=
cos x cos ycos z
cos x cos y cos z
sin x cos y
cos x sin y
sin y cos z
cos ysin z
−=−
cos x cos y
cos x cos y
cos ycos z
cos ycos z
sin x
sin y
sin y
sin z
−=−
cos x
cos y
cos y
cos z
⇒ −=−
tan x
tan y
tan y
tan z
⇒ tan
x
+
tan z
=
2 tan y
⇒ tan x, tan y, tan z are in A.P.
⎛⎞⎛⎞
2
π
4
π
21.
If
xy =
cos
θθ
cos
⎝⎠⎝⎠ for some θ ∈ R then show that
+=
z
cos
θ
+
⎜⎟⎜⎟
3
3
xy ++=yz
zx
0
Solution:
⎛⎞⎛⎞
2
π
4
π
Let
xy cos =
θθ
cos
+=
z
cos
θ
+=
k
⎜⎟⎜⎟
⎝⎠⎝⎠ 3 3
kk
⎛⎞
2
π
⎛⎞
4
π
k
cos
θθ
=
cos
+=
: cos
θ
+=
⎜⎟
⎜⎟
xy
⎝⎠
3
⎝⎠ 3
z
2
π
⎞⎛
4
π
kkk ++=
cos
θθ
+
cos
+
cos
θ
+
⎟⎜ +
x
y
2
⎜ ⎝
33 ⎠⎝
⎠ ⎟
kkk
++= 0
{ Refer the problem (1) in short answer question)
x
4
2
xy ++=yz
zx
0

www.sakshieducation.com

www.sakshieducation.com

22. If neither A or A + B is an odd multiple of π/2 and if m sin B = n sin(2A + B) then prove that (m+n) tan A = (m–n) tan (A+B).

Sol. Given m sin B = n sin(2A + B)

m
sin(2A
+
B)
=
n
sin B
By componendo and dividendo, we get
m
+
n
sin(2A
++
B)
sin B
=
m
n
sin(2A
+− B)
sin B
2sin(A
+ B)cos A
=
2cos(A
+ B)sin A
m
+
n
=
tan(A
+
B)cot A
m
n
(m
+
n)
=−
(m
n) tan(A
+
B)
cot A
(m
+
n) tan A
=− (m
n) tan(A
+
B)
23.
If tan ()AB+= λ tan ()AB−
then show that
()λ + 1 sin 2 B =−()λ
1 sin 2 A
Solution:
tan
(
AB
+
)
λ
sin
(
AB
+−
)
cos
(
AB
)
λ
=
×
=
tan
(
AB
)
1
cos
(
AB
++
)
sin
(
AB
)
1
Using componedo and dividendo
sin
(
A
+
B
)(
cos
AB
−+
)
cos
(
AB
+
)
. sin
(
AB
)
λ + 1
=
sin
(
AB
+
)
cos
(
AB
−−
)
cos
(
AB
+
)(
sin
AB
)
λ −
1
sin 2 A
λ
+ 1
=
()
λ
1
sin 2
A
=+
()
λ
1 sin 2
B
sin 2
B
λ − 1
LAQ’S
24.
If A, B, C are the angles of a triangle then prove that
(i)
sin 2 A −+=sin 2 B
sin 2C
4cos ABCsin
(ii)
cos 2 A − cos 2 B + cos 2C =−1
cos
4 sin A cos BCsin
Solution :
0
0
(i)
ABC++= 180 ⇒ AB+= 180 − C sin AB+
(
)
= sin C
0
C
= 180
−+AB
()
sin C = sin AB+
()
cos( AB+
) =− cos C
sin 2 A − sin 2 B + sin 2C = 2cos( AB+
)(sin AB−+)
2sin C cos C
=−
2cos C sin ( AB+
) + 2sin C cos C
=+
2cos C ⎡− ⎣ sin
(
AB− )(+ sin AB+
)⎤
= 2cos C [2cos ABsin
] = 4cos ABCsin
cos

(ii)

(

cos 2 A cos 2 B + cos 2C =− 2 sin AB+

)(

. sin AB

)

+ 1 2sin

=−1

(

2sin C . sin AB

)

2

2sin C

2

C

www.sakshieducation.com

www.sakshieducation.com

=−1

=−1

 2sin C { sin ( ) AB− + sin C } 2sin C { sin ( AB+ + sin )( AB+ )}
=−1
2sin C {2sin A cos B} =−1
2sin A cos BCsin
25.
If A, B, C are angles of a triangle then prove that
(i)
sin ABC+−=sin
sin
4sin A / 2 sin B / 2 cos C / 2
A
B
C
(ii) cos
ABC+
cos
cos
=−
1
+
4cos
cos
sin
222
Solution :
⎛ A
+
B
AB ⎞
C
C
(i)
sin
ABC
+−=
sin
sin
2sin
2sin
cos
⎜ ⎝
2
⎟⎜ ⎞⎛ cos
⎠⎝
2
22
C ⎞
⎛ A − B ⎞
CC
0
=−
sin
90
cos
2sin
cos
⎝ ⎜
2
⎟ ⎠
⎜ ⎝
2
⎟ ⎠
22
C
C ⎫
=
2cos
cos
A − B ⎞
sin
22
2
C
⎛ A − B ⎞⎛ AB+
⎞⎫
=
2cos
cos
cos
22
2
⎠⎝ ⎟⎜
⎠⎭ ⎟
C ⎧
= 2cos
2sin
AB sin ⎫
2
22
= 4sin ABC/ 2 sin
/ 2 cos
/ 2
Solution
⎛ AB
+
AB ⎞
(ii)
cos
A
+
cos
B
−= coC
2cos
C
⎜ ⎝
2
⎟⎜ ⎞⎛ cos
⎠⎝
cos
2
⎟ ⎠
C ⎫
0
2
=
2cos ⎛⎞C ⎜ 90
cos
−− ⎨ 1
2sin
⎛ A − B ⎞
⎝⎠ 22 ⎝
⎠ ⎟
2
C
⎛ A − B ⎞
C
2
=
2sin
cos
−+
1
2sin
22 ⎝
⎛ A − B ⎞
2
C ⎧
C ⎫
−+
1
2sin
cos
+
sin
22
2
C
⎛ A − B ⎞⎛
AB+ ⎞⎫
0
=−
1 ⎨
+
2sin
cos
+
sin 90
⎟⎜
2
⎝ ⎜
2
⎠⎝
2
⎠⎭
C
⎛ A − B ⎞⎛ AB+
⎞⎫
=−
1 ⎨
+
2sin
cos
+
cos
⎟⎜
22
⎠⎝
2
⎠⎭ ⎟
C ⎧
=−
1
+
2sin
2cos
AB cos ⎫
2
22
A
B
C
=−
1
+
4cos
cos
sin
222

www.sakshieducation.com

www.sakshieducation.com

26. If A, B, C are the angles of a triangle then prove that

(i)

(ii)

sin A +−=sin B sin C 2sin ABsin cos C

2 sin ABsin

222

222

A + cos

cos

B cos C =−1

cos C

Solution:
0
(i)
ABC++= 180
2222
sin
A +−=++sin
B
sin
C
sin
A
sin BC
(
)(
sin BC−
)
{
2
2
∵ sin
B −=+sin C
sin BC
(
)(
sin BC−
)}
2
(
0
=+sin A sin 180 − A sin BC−
)
(
)
2
=+sin A sin A sin BC−
(
)
= sin A
{ sin A +−sin BC
(
)}
{ sin 180
(
0
= sin A
−+BC
)
+ sin BC−
(
)}
= sin A sin BC++ sin
{
()()}
BC−
=
sin A {2sin BCcos
} = 2sin ABCsin
cos
Solution :
222
2
22
(ii)
cos
ABC+−==cos
cos
cos
A
{
cos C − cos
B
}
2
=
cos
A −+sin BC
(
)(
sin BC−
)
2
(
0
=−1
sin
A − sin
180
− A
)
sin BC−
(
)
2
=−1 sin
A − sin A sin BC−
(
)
=−1
sin A sin A + sin BC−
{
(
)}
{
(
0
)
(
)}
=−1
sin A sin 180
− BC+
+ sin BC−
=−1
sin A sin BC+
{
(
)(
+ sin BC−
)}
=
1 −
sin
A {2sin BCcos
}
= 1 − 2sin ABCsin
cos
0
27.
If
ABC++= 180
then prove that
A
B
C
ABC ⎫
222
(i)
cos
+
cos
+
cos
=+ 2 ⎨ 1
sin
sin
sin
2
2
2
222
A
B
C
ABC
222
(ii)
cos
+−=
cos
cos
2cos
sin
sin
2
2
2
222
0
0
Here
ABC++= 180
= A / 2 + B / 2 + C / 2 = 90
Solution:
ABC
A
2222
2
2
(i)
cos
+
cos
+
cos
=
cos
+−
1
sin
B
/ 2
+
cos
C
/ 2
2222
C
22
2
=+ 1
cos
AB sin ⎫
+
cos
22
2
⎛ AB ⎞⎛
AB ⎞
C
2
=+ 1
cos
+
⎟⎜ cos
+
cos
⎜ ⎝
22
⎠⎝
22
2

www.sakshieducation.com

www.sakshieducation.com

=+ 1

cos 90

0

 C ⎞⎛ AB ⎞ − +− 1 sin 2 C 2 ⎟⎜ cos ⎠⎝ 22 ⎟ ⎠ 2
C
⎛ A − B ⎞
C
2
=+
2
sin
cos
sin
22 ⎝
2
C
A
− B
C
=+
2
sin
cos
sin
22
⎠ ⎟
2
C
A
− B
⎞⎛
AB+
⎞⎫
0
=+
2
sin
cos
sin 90
_
⎟⎜
22
⎠⎝
2
⎠⎭ ⎟
C
A
− B
⎞⎛
AB+
⎞⎫
=+
2
sin
cos
cos
22
⎠⎝ ⎟⎜
2
⎠⎭
A
B
C
2
+
2sin
sin
sin
222
A
B
C
=
2
+
2cos
cos
cos
222
ABC
A
2222
22
(ii)
cos
+−=−
cos
cos
cos
cos
CB cos ⎫
2222
22
A
⎛ BC+
⎞⎛ BC−
2
=
cos
sin
22 ⎝
⎟⎜ . sin
⎠⎝
2
⎠ ⎟
A
A ⎞
C ⎞
2
0
=−
cos
sin
90
sin
⎛ B −
2
⎜ ⎝
22 ⎠ ⎝
⎟ ⎠
A
A
2
2
=
cos
cos
sin
22
⎛ B −
⎜ ⎝
C ⎞
2
⎟ ⎠
A
A
=
cos
cos
sin
22 ⎩
B − C ⎫
2
A
B + C
⎞⎛
BC−
⎞⎫
0
=
cos
cos 90
−−
sin
⎟⎜
2
22
⎠⎝
⎠⎭ ⎟
A
BC+
⎞⎛
BC−
⎞⎫
A
B
C
=
cos
sin
−=
sin
2cos
sin
sin
⎟⎜
2
⎜ ⎝
2
⎠⎝
2
⎠⎭ ⎟
222
28.
In a triangle ABC prove that
⎛ πππ−−−ABC⎞⎛ ⎞⎛
(i) cos
ABC ++=
cos
cos
4cos
⎟⎜ cos
⎟⎜ cos
222
⎝ ⎜
4
⎠⎝
4
⎠⎝
4
⎠ ⎟
⎛ πππ++−ABC⎞⎛ ⎞⎛
(ii) cos
ABC +−=
cos
cos
4cos
222
⎝ ⎜
4
ABC
⎛ π
(iii) sin
+
sin
sin
=−
1
+
4 cos
cos
⎠⎝ ⎟⎜
− A ⎞
⎟ ⎠
⎟⎜ cos
4
⎠⎝
4
⎠ ⎟
⎛ ππ−−BC⎞⎛
cos
⎟⎜ sin
222
⎜ ⎝
4
⎝ ⎜
4
⎠⎝
4
⎠ ⎟
Solution:
(i)
Given ABC++
= π
πππ−−−ABC⎞⎛ ⎞⎛
ππ−−AB⎞⎛
⎞⎫⎧
π − C
⎞⎫
R.H S
4cos
cos
cos
=
2
cos
cos
2cos
⎟⎜
⎟⎜
⎟⎜
⎬⎨
⎝ ⎜
444
⎠⎝
⎠⎝
⎟ ⎠
44
⎜ ⎝
⎠⎝
⎠⎭⎩
⎜ ⎝
4
⎠⎭ ⎟

www.sakshieducation.com

www.sakshieducation.com

=

cos

⎛ ⎜ ⎝

ππ−+−A

B

⎞⎛

⎟⎜

⎠⎝

ππ−−+AB

⎞⎫⎧

⎬⎨

⎠⎭⎩

⎜ ⎝

π

C

4

4

+

cos

2cos

{

()()}

2cos A cos B = cos AB++ cos AB+

⎞⎫

⎠⎭ ⎟

⎧π
⎛⎞AB+
⎛⎞⎛⎞AB−−⎫
π
C
=−
⎨⎨ cos
+
cos
2cos
⎜⎟
⎜⎟⎜⎟
24 ⎝⎠⎭
⎝⎠⎝⎠ 4 ⎭ 4
π −+C
AB ⎞
⎛ π
− C ⎞⎛ AB−
π
AB+ ⎞⎛ AB+ ⎞
=
2cos
sin
+
2cos
⎟⎜ cos
cos
44 ⎝
⎠ ⎟
⎜ ⎝
4
⎠⎝
4
⎟ ⎠
⎜ ⎝
24
⎟⎜ = sin
⎠⎝
4
⎟ ⎠
⎛ πππ−++C
AB
⎞⎛
−−−C
AB ⎞
−+−C
AB ⎞
=−+
sin
sin
cos
+
cos
⎟⎜
44 ⎠⎝
⎟ ⎠
⎜ ⎝
4
⎠ ⎟
⎛ π −−+C AB ⎞
⎜ ⎝
4
⎠ ⎟
⎧ ∵ 2cos
A
sin
B
=
sin
(
AB
+−
)(
sin
AB − ⎫ ⎪
)
2cos
A
cos
B
=
cos
()()
AB
++
cos
AB
⎭ ⎪
π − C + π − C
⎞⎧
A + B +−−CCA − B
A + B + C − C + A − B
∴−
sin
sin
+
cos
⎝ ⎜
44
⎠⎩
⎝ ⎜
4
⎠ ⎟
ABCC AB
++−−+
⎧ ∵
π
=++
ABC
+ cos
⎬⎨
π
4
a dA
+=−
B
C
π
C
AB +
=
sin
−+
cos
cos
⎜ ⎝
22
⎟ ⎠
2
2
A
B
C
=++
cos
cos
cos
222
Solution :
⎛ πππ++−ABC⎞⎛ ⎞⎛ ⎞
(ii)
R.H.S
= 4cos
⎟⎜ cos
⎟⎜ cos
⎝ ⎜
444
⎠⎝
⎠⎝
⎠ ⎟
ππ++A ⎞⎛
B
⎞⎫
π − C
=
2cos
cos
⎟⎜
2cos
⎝ ⎜
44
⎠⎝
⎠⎭ ⎟
⎜ ⎝
4
⎟ ⎠
ππ+++A
B
⎞⎛
π +−ABπ −
⎞⎤
π − C
=
cos
+
cos
2cos
⎟⎜
⎟⎥
4
⎠⎝
44
⎠⎦
⎟ ⎠
π
A +−B ⎞⎛
AB
⎞⎤
π − C
=++
cos
cos
2cos
⎟⎜
⎝ ⎜
24
⎠⎝
4
⎟⎥ ⎠⎦
⎝ ⎜
4
⎠ ⎟
⎛ π −+C ⎞⎛
AB ⎞
=−
2cos
⎟⎜ sin
+
2cos
cos
⎝ ⎜
44 ⎠⎝
⎟ ⎠
⎛ π − C ⎞
⎟ ⎠
⎜ ⎝
4
⎜ ⎝
A − B ⎞
⎟ ⎠
4
ππ− C
⎞⎛
⎛ π − C + A − B ⎞ +
=−
2cos
⎟⎜ sin
− C ⎞
+
cos
cos
⎝ ⎜
44 ⎠⎝
⎝ ⎜
4
⎟ ⎠
⎛ π − CA−+ B ⎞
⎟ ⎠
⎜ ⎝
4
⎛ π
A + B + C
−−A
B ⎞⎛ A ++B
=−
sin 2
− C ⎞
+
cos
cos
⎝ ⎜
44 ⎠ ⎝
⎟⎜ ⎠⎝ +
C − C −+AB ⎞
⎟ ⎠
4
π
C
AB +
=−
sin
+
cos
cos
⎝ ⎜
22
⎠ ⎟
2
2
A
B
C
=+−
cos
cos
cos
222

www.sakshieducation.com

www.sakshieducation.com

 Solution : (iii) R.H.S =− 1 + 4cos
 ⎞ . sin ⎟⎜ cos 44 ⎠⎝ ⎠ ⎟ ⎝ ⎜ 4

ππ−−AB⎞⎛

⎜ ⎝

π C ⎞ ⎟ ⎠

ππ−−A ⎞⎛
B
⎞⎫
π − C
=− 1
+ ⎨
2cos
cos
2sin
⎟⎜
⎜ ⎝
44
⎠⎝
⎠⎭ ⎟
⎜ ⎝
4
⎟ ⎠
π
⎛⎞AB+
AB−−⎫
⎛⎞π
C
=−
1
+
cos
+
cos
2sin
⎜⎟
24 ⎝⎠ ⎠
4
⎝⎠ ⎜⎟ 4
⎛ AB+−⎞⎛ π
C ⎞
⎛ π − C ⎞
⎟ ⎠
⎛ AB−
=−
1
+
2sin
⎟⎜ sin
+
2sin
cos
⎝ ⎜
44 ⎠⎝
⎟ ⎠
⎜ ⎝
4
⎜ ⎝
4
⎟ ⎠
π − C
⎞⎛
A + BC+− C + A − B
A + B + C − C − A + B
=−
1
+
2sin
+
sin
+
sin
⎟⎜
⎝ ⎜
44
⎠⎝
⎠ ⎟
4
π
− C ⎫
A
B
2
=−
1
2sin
4
+
sin
+
sin
22
A
B
=−
cos
+
sin
+
sin
⎝ ⎜
⎛ π − C ⎞
⎟ ⎠
2
22
A
B
C
=+−
sin
sin
sin
222
0
29.
If
ABC++= 90
then prove that
cos 2 ABC+ cos 2
+ cos 2
= 1 + 4sin ABCsin
sin
Solution :
cos 2 A + cos3 B + cos 2C = 2cos( AB+
)(cos AB−+)
cos 2C
0
0
=
2cos 90
(
− C
)
cos AB−
(
)
+ cos 2C ∵ AB+= 90
{
− C
}
2
=
2sin C cos AB−
(
)
+−1
2sin C
=+1
2 sin C cos AB−
{
(
)
− sin C
}
=+1
2sin cos
{
(
A − B
)
(
0
− sin 90
−+AB
)}
=+1
2sin C cos AB−
{
()()}
− cos AB+
=
1 + 2sin C {2sin ABsin
}
= 1 + 4sin ABCsin
sin
0
30.
If
ABC+
+= 270
then prove that
2
22
(i)
cos
A + cos B − cos C=− 2cos ABcos
sin C
(ii)
sin 2 A+ sin 2 B − sin 2C =− 4sin ABCsin
cos
Solution:
2
2
2
2
22
(i)
cos
A +−=−−cos
B
cos
C
cos
A
{
cos CBcos
}
2
=
cos
A −+sin BC
(
)(
sin BC−
)

2

=−cos A

=+cos

2

A

sin

(

270

0

A

)

sin

(

cos A sin BC

(

)

BC

)

www.sakshieducation.com

⎫ ⎬

www.sakshieducation.com

= cos A cos A +−sin BC

{

(

)}

= cos A cos 270

{

(

0

−+BC

)

(

+ sin BC

)

}

cos A − sin BC−+ sin ( BC−
{
(
)
)
}
− cos
A (2cos BCsin
) =− 2 cos A cos B sin C
(ii)
sin 2 A+ sin 2 B − sin 2C =− 4sin ABCsin
cos
2sin ( AB+
)(cos AB−−)
sin 2C
0
2sin
(
270
− C
)
cos AB−− sin 2C
(
)
−2cos C cos( AB−−)
2sin C cos C
0
−2cos ⎡cos( ⎣ AB−
) + sin (220
−+AB )⎤ ⎦
−2cos C [cos( AB−−)
cos ( AB+
)]
−4sin ABCsin
cos
0
31.
If
ABC+
+= 0
then prove that
(i)
sin 2 A + sin 2 B + sin 2C =− 4sin ABCsin
sin
A
B
C
(ii) sin
ABC+
sin
sin
=−
4cos
cos
sin
2
22
Solution :
A
BC
AB
C
0
0
(i)
ABC++=
0
++=
0
+
=−
222
22
2
sin 2 A + sin 2 B + sin 2C = 2sin( AB+
)cos( AB−+)
sin 2C
=
2sin ()−C cos( AB−+)
sin 2C
=− 2sin C cos( AB−
) + 2sin C cos C
=−2sin C [cos( AB−
) − cos C ]
⎡ ∵
C
=−
(
AB +
)
=− 2sin C ⎡cos()()AB− ⎣ − cos AB+
⎦ ⎤
cos
C
=
cos(
AB
+
)
⎦ ⎥
=
− 2sin C {2sin ABsin
}
= −4sin ABCsin
sin
Solution :
⎛ AB
+
AB ⎞
(ii)
sin
ABC
+−=
sin
sin
2sin
⎟⎜ ⎞⎛ cos
⎠⎝
=
sin
C
⎝ ⎜
2
2
⎠ ⎟
C ⎞
CC
=− 2sin ⎜
cos
A − B ⎞
⎟ ⎠
2sin
cos
2
⎟ ⎠
⎝ ⎜
2
22
C
A
− B
C ⎤
=−
2sin
cos
+
cos
22
⎜ ⎝
⎟ ⎠
2
C
A
−B
⎞⎛
AB+
⎞⎤
=−
2sin
cos
+
cos
⎟⎜
22
⎜ ⎝
⎠⎝
2
⎠⎦ ⎟⎥
C ⎡
= − 2sin
2cos
AB cos ⎤
2
⎢ ⎣
22
⎥ ⎦

www.sakshieducation.com

www.sakshieducation.com

=

4cos

A

cos

B

sin

C

2

22

0
32.
If
ABCD+++= 360
then prove that
⎛ A
++⎞⎛
B
AC
+
(i) sin
A
sin
B
+
sin
CD
sin
=−
4cos
⎟⎜ sin
cos
⎜ ⎝
222
⎠⎝
⎟ ⎠
⎝ ⎜
⎠ ⎟
(ii)
cos 2 A +++=cos 2 B
cos 2C
cos 2 D
4cos( AB+
)(cos AC+
)
Solution:
ABCD
0
0
(i)
A + B ++CD =
360
+++=
180
2222
A + B
CD+ ⎞
0
=− ⎜
180
2
2
⎟ ⎠
⎛ AB
+−⎞⎛
AB
⎟ ⎠ +
CD
+
CD ⎞
sin
ABCD
−+−=
sin
sin
sin
2cos
⎟⎜ sin
2cos
⎜ ⎝
22 ⎠⎝
⎝ ⎜
2
⎟⎜ ⎞⎛ sin
⎠⎝
2
⎟ ⎠
⎛ AB
+−⎞⎛
AB
AB
+−⎪
CD
0
= 2cos
sin
++
2cos 180
⎟⎜
sin
⎝ ⎜
22
⎠⎝
⎠ ⎟
22
⎪ ⎩
⎪ ⎭
⎜ ⎝
⎟ ⎠
⎛ AB+−⎞⎛ AB ⎞
⎛ AB+−⎞⎛ CD ⎞
=
2cos
⎟⎜ sin
2cos
⎟⎜ sin
⎝ ⎜
22 ⎠⎝
⎠ ⎟
⎝ ⎜
22 ⎠⎝
⎟ ⎠
A
+−B ⎞⎛⎧ AB
CD−
⎞⎫
2cos
sin
sin
⎟⎜
⎝ ⎜
22
⎠⎝⎩
⎠ ⎟
⎝ ⎜
2
⎠⎭ ⎟
A + B
A + B +−CD
⎞⎛
A − B − C + D
⎞⎫
2cos
2cos
. sin
⎟⎜
⎝ ⎜
24
⎠⎝
4
⎠⎭
0
0
A + B
4cos
⎧ A + C −
360
++AC ⎫⎧ A + D −
360
cos
⎬⎨
sin
⎜ ⎝
24
⎟ ⎠
4
⎭⎩
+ A + D ⎫
⎛ AB++⎞
AC
0
0
4cos
cos
22 ⎠ ⎩
90
⎬⎨ sin
90
⎝ ⎜
⎭⎩
2
AB++⎞
AC
0
0
4cos
90
90
⎝ ⎜
cos
22 ⎠ ⎩
⎫⎧ ⎬⎨ sin
⎭⎩
2
⎛ AB++⎞⎛ A
C ⎞
A +
D ⎞
− 4cos
⎟⎜ sin
cos
⎜ ⎝
22 ⎠⎝
⎟ ⎠
⎜ ⎝
2
⎟ ⎠
(ii)
cos 2 A + cos 2 B + cos 2C + cos 2 D = 2cos( AB+
)(cos AB−+)
2cos(CD+
) . cos(CD−
)
= 2cos A +
(
B
)(
cos A
− B
)
+
(
0
2cos 360 −+A
B
)
. cos CD−
(
)
=
2cos( A
+
B )(cos A
−+B )
2cos( A+ B )(cos CD−
)
= 2cos AB+
(
)({
cos AB−+ cos CD−
)
(
)}
ABCD
++−
⎞⎛
ABCD
−−+
⎞⎫
=
2cos(
A
++
B
)
2 cos
cos
2
2
⎝ ⎜
⎠⎝ ⎟⎜
⎠⎭ ⎟
(
B
+
D
)(
)
−+
AC
(
⎪⎪ ⎫⎧
B
+−
C
)(
A
+
)
4cos
(
A
+
B
)
cos
⎬⎨ cos
2
2
⎪⎪ ⎭⎩
D ⎫ ⎪
⎪ ⎭

4cos

(

A

+

B

)

cos

360

0

−+

2

(

AC

)

2

⎫⎧ ⎪⎪

⎬⎨ cos

⎭⎩ ⎪⎪

360

0

−+ 2 AD ⎫ ⎪ ⎬ ⎪ ⎭

2

)

(

www.sakshieducation.com

www.sakshieducation.com

4cos AB + cos ⎡ ⎣ 180

(

)

0

A

−+

C

0

−+ A

D

cos 180

(

{

(

)}{

(

)}{

(

)}

)

4cos( AB+++)(cos AC )(cos AD )
33.
If A ++=B
C
2 S then prove that
SA
S
B
C
(i)
sin ()()sin
sA
−+
sB
−+
sin
C
=
4cos
sin
⎜ ⎝
2
⎟⎜ ⎞⎛ cos
⎠⎝
22 ⎠
sA
⎞⎛
s
B
C
(ii) cos()
sA
+
cos()
sB
+
cos
C
=−
1
+
4cos
cos
cos
⎝ ⎜
2
⎠⎝ ⎟⎜
22
⎠ ⎟
Solution :
(i)
sin ()()sA− + sin sB−+ sin C
⎛ 2
sA
−−
B
B
A
=
2cos
2
⎟⎜ ⎞⎛ cos
⎠⎝
+
sin
C
⎜ ⎝
2
⎠ ⎟
C
A − B
CC
=
2sin
cos
+
2sin
cos
2
⎜ ⎝
2
⎟ ⎠
22
C
A − B
C
=
2sin
cos
+
cos
22
⎠ ⎟
2
C
ABC−+
⎞⎛
ABC−−
⎞⎫
=
2sin
2cos
. cos
24
⎠⎝ ⎟⎜
4
⎠⎭ ⎟
C
⎛ 2
sBB−− ⎞⎛
= 4sin
cos
⎟⎜ cos
2 sAA−− ⎞⎫
24 ⎝
⎠⎝
4
⎠⎭
⎛ sA− ⎞⎛ sB−
C
4cos
⎟⎜ cos
sin
⎝ ⎜
2
⎠⎝
22 ⎠
Solution (ii)
cos()sA−+ cos()sB−+ cos C
⎛ 2 sAB −−
BA
=
2cos
⎟⎜ ⎞⎛ cos
⎠⎝
cos C
⎜ ⎝
2
2
⎞ ⎟ ⎠ +
C
⎛ BA−
C
=
2
2cos
cos
+
2cos
1
22 ⎝
⎟ ⎠
2
C
B − A
C ⎤
= −+
1
2cos
cos
+
cos
22
2
⎠ ⎟
C ⎡
⎛ B −+A
C ⎞⎛ B −−AC ⎞⎤
= 2cos
1
+
2cos
⎟⎜ cos
24 ⎝
4
⎠⎝
⎟⎥ ⎠⎦
C
⎛ B +−C
A ⎞⎛ AC+− B ⎞
= 4cos
1
+
cos
⎟⎜ cos
24 ⎝
⎠⎝
4
⎠ ⎟
C
⎧ 2
s
−−AA ⎫⎛ cos
= 4cos
1
+
cos
24 ⎩
⎭⎝
2 sBB−− ⎞
⎠ ⎟
4
C
⎛ S − A ⎞⎛ sB− ⎞
1
+
4cos
cos
⎟⎜ cos
= 22 ⎝
⎠⎝
2
⎠ ⎟

=

1

+

4cos

⎜ ⎝

SA−−−⎞⎛ SB

cos

⎠⎝ ⎟⎜

⎞⎛

cos

⎠⎝ ⎟⎜

SB

⎟ ⎠

C

2

2

cos

22

www.sakshieducation.com

www.sakshieducation.com

34. If A,B,C are angles of a triangle then prove that

sin

A

B

222

+

sin

sin

2

2

 C AB C 1 =− 2cos cos cos

2

222

SOL.
A+B+C = 180 0
ABC
222
LHS =+−
sin
sin
sin
222
A
BC
BC
2
=++
sin
sin
2
⎜ ⎝
22
⎟⎜ ⎞⎛ .sin
⎠⎝
22
⎟ ⎠
A
A
BC
2
=+
sin
sin ⎜ ⎛ 90
2
2
⎟⎜ ⎞⎛ .sin
⎠⎝
22
⎟ ⎠
A
A
BC
2
=1-cos
+
cos
.sin
2
2
⎝ ⎜
22
⎠ ⎟
A
A
BC
⎞ ⎞
=− 1
cos
cos
sin
2
2
22
⎠ ⎠
A
BC
⎞⎛ ⎞ −
BC ⎞ ⎞
=1
cos
cos 90
−+
sin
⎟⎜⎟
2
⎜ ⎝
22
⎠⎝⎠
22
⎟ ⎠
A
BC
⎞⎛
BC ⎞ ⎞
=−
1
cos
sin
+
sin
⎟⎜
2
⎜ ⎝
22
⎠⎝
22
⎠ ⎠
A
BC
=
1
cos
2cos
sin
2
⎜ ⎝
22
⎟ ⎠
A
BC
=− 1
2cos
cos
sin
=
RHS
2
22
35. If A+B+C =3π/2 , prove that cos2A+cos2B+cos2C =1- 4sinA.sinB.sinC
36. 13. If A,B,C are angles of a triangle, then prove that
A
BC
πππ−−−A
B
C
sin
+
sin
+
sin
=+ 1
4sin
+
sin
+
sin
222
4
4
4

www.sakshieducation.com

www.sakshieducation.com

37. If A, B, C are the angles of a triangle then prove that cos2A+cos2B+cos2C = -4cosAcosBcosC-1

cos2A+cos2B+cos2C =
22
AB
+
22
AB
=
2cos
cos
+
cos 2 C
2
2
= 2cos
(
AB
+
)(
cos
AB
−+
)
2cos
2 C
1
= 2cos
(
π −
c
)(
cos
AB
−+
)
2cos
2 C
1
=−
2cos
C
cos
(
AB
)
+
2cos
2 C
1
= (
2cos
C
(
cos
AB
−+
)
cos
C
) −
1
= 2cos
C
(
cos
()
AB
−+
cos
(
π
−+
()))
AB
1
= ()())
2cos
C
(
cos
AB
−−
cos
AB
+
1
=−
2cos
C
(
2cos
AB cos
)
1
=−
4cos
ABC
cos
cos
1

www.sakshieducation.com